Thermodynamics, thermal performance and climate change: temperature regimes for bumblebee (Bombus spp.) colonies as examples of superorganisms - Kevan, Peter G.; Rasmont, Pierre; Martinet, Baptiste (Frontiers in Bee Science, 2024)
Evidence is widespread that many species of Bombus are in population and biogeographical decline in response to adverse effects of global climate warming. The complex interactions of the mechanisms at the root of the declines are poorly understood. Among the numerous decline factors, we posit that heat stress in the nests could play a key role in the decline of bumblebee species. The similarity of the optimum temperature range in incubating nests is remarkable, about 28 -32 C regardless of species from the cold High Arctic to tropical environments indicates that the optimal temperature for rearing of brood in Bombus spp. is a characteristic common to bumblebees (perhaps a synapomorphy) and with limited evolutionary plasticity. We do note that the brood rearing temperature for the boreal and Arctic species that have been tested is stressfully high when compared with that for B. terrestris.The Thermal Neutral Zone (TNZ), temperatures over which metabolic expenditure is minimal to maintain uniform nest temperatures, has not been studied in Bombus and may differ between species and biogeographic conditions. That heat stress is more serious than chilling is illustrated by the Thermal Performance Curve Relationship (TPC) (also sometimes considered as a Thermal Tolerance Relationship) which indicates that development and activity increase more slowly as conditions become warmer until reaching a plateau of the range of temperatures over which rates of activity do not change markedly. After that, activity rates decline rapidly, and death ensues. The TPC has not been studied in eusocial bees except Apis dorsata but may differ between species and biogeographic conditions. The importance of the TPC and the TNZ indicates that environmental temperatures in and around bumblebee nests (which have been rarely studied especially in the contexts of nest architecture and substrate thermal characteristics) are factors central to understanding the adverse effects of heat stress and climatic warming on bumblebee populations, health, and biogeographical decline.